Electromechanical delay in the tibialis anterior muscle during time-varying ankle dorsiflexion - Úbeda, A.; Del Vecchio, A.; Sartori, M.; Puente, S. T.; Torres, F.; Azorín, J. M.; Farina, D. (IEEE International Conference on Rehabilitation Robotics, 2017)
We evaluated the electromechanical delay (EMD) for the tibialis anterior (TA) muscle during the performance of time-varying ankle dorsiflexions. Subjects were asked to track a sinusoidal trajectory, for a range of amplitudes and frequencies. Motor unit (MU) action potential trains were identified from surface electromyography (EMG) decomposition and summed to generate the cumulative spike train (CST). CST and the exerted force were cross-correlated to identify the delay between the CST and force, which was considered as an estimate of the EMD. The results showed that the EMD decreased logarithmically with the increase in the slope of the force produced.
CRIS-Team Scopus Importer:2020-10-12